2016
DOI: 10.1111/sapm.12117
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation of Soliton Families from Linear Modes in Non‐‐Symmetric Complex Potentials

Abstract: Continuous families of solitons in the nonlinear Schrödinger equation with non‐scriptPT‐symmetric complex potentials and general forms of nonlinearity are studied analytically. Under a weak assumption, it is shown that stationary equations for solitons admit a constant of motion if and only if the complex potential is of a special form g2(x)+ig′(x), where g(x) is an arbitrary real function. Using this constant of motion, the second‐order complex soliton equation is reduced to a new second‐order real equation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 33 publications
(87 reference statements)
2
38
2
Order By: Relevance
“…Notably, the conditions for the existence of continuous families of solitary waves are much more general than those corresponding to PT-symmetry or to the aforementioned special form of the complex potential. The latter appears as a necessary condition for the existence of a homoclinic orbit, corresponding to a solitary wave, when starting from the linear modes of the inhomogeneous system [47]. On the contrary, in our approach, the starting point consists of the homogeneous nonlinear system which is integrable and features a homoclinic orbit, and our conditions ensure its persistence under inhomogenous perturbations, so that the resulting continuous families of solitary waves bifurcate from the nonlinear modes of the homogeneous system.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Notably, the conditions for the existence of continuous families of solitary waves are much more general than those corresponding to PT-symmetry or to the aforementioned special form of the complex potential. The latter appears as a necessary condition for the existence of a homoclinic orbit, corresponding to a solitary wave, when starting from the linear modes of the inhomogeneous system [47]. On the contrary, in our approach, the starting point consists of the homogeneous nonlinear system which is integrable and features a homoclinic orbit, and our conditions ensure its persistence under inhomogenous perturbations, so that the resulting continuous families of solitary waves bifurcate from the nonlinear modes of the homogeneous system.…”
Section: Introductionmentioning
confidence: 88%
“…Although wave localization in PT-symmetric complex potentials has been well-studied, and the existence of continuous families of solitary waves has been shown [36], the existence of such families in non-symmetric complex potentials is still under investigation. Recently, continuous families of solitary waves were found to exist [41][42][43][44][45] in non-PT-symmetric potentials of a special form (so-called Wadati-type) [46]; it has been shown that such form is a necessary condition for the existence of continuous solitary wave families bifurcating from the linear modes of the system [47].…”
Section: Introductionmentioning
confidence: 99%
“…Generalized Wadati-like potentials of the form W 2 (x) + aW (x) + idW (x)/dx were considered in Refs. [105][106][107][108], and it was shown that these special potentials are all the 1D potentials which admit bifurcation of asymmeric soliton families…”
Section: Solitons In Localized Potentialsmentioning
confidence: 99%
“…In the present work, we revisit these considerations. In particular, we discuss the results of the important contribution of [22]. This work suggests (and indeed conjectures) that the only complex potentials that could feature continuous families of stationary solutions although non-PT -symmetric are the ones of the Wadati type.…”
Section: Introductionmentioning
confidence: 66%